Time-optimal, minimum-jerk, and acceleration continuous looping and stitching trajectory generation for 5-axis on-the-fly laser drilling. (15th April 2019) - Alzaydi, Ammar
Highlights: Novel idea of applying optimized trajectories for laser drilling passes. Developed algorithms have been applied on gas turbine combustion chamber panels. Proposed technique provides over 6% reduction in cycle time. 56% reduction in the integral square of jerk as been achieved (vibration reduction). Minimization in vibrations on laser optics significantly reduced. Abstract: The process of on-the-fly laser drilling is capable of achieving high throughputs and offers a highly productive approach for producing pre-defined groups of holes (clusters) to be laser drilled on freeform surfaced parts. On-the-fly drilling also presents different technological requirements, needing a different kind of trajectory optimization solutions. Current machine tool controllers are not equipped with appropriate trajectory functions that can take full advantage of the achievable laser drilling speeds. This paper presents the novel idea of applying optimized looping and stitching trajectories (by solving for time optimal trajectories for individual machine axis and choosing the minimum value of the integral square of jerk) for looping a cluster during multiple laser drilling passes, or making a connection between consecutive clusters with given position and velocity boundary conditions. While finding the minimal motion cycle time and minimizing vibrations transmitted to the laser optics causing misalignment (requiring significant manufacturing stoppage for optics realignment). The produced smooth and time optimal trajectories, hand-in-hand with cluster trajectory optimization, proved to reduce both the total drilling cycle time and vibrations transmitted through 5-axis machine to the laser optics. In detail, when compared to currently used on-the-fly drilling methods in industry today (Ex. at Pratt and Whitney Canada), ∼6% reduction in overall cycle time was observed for specific part examples due to the avoidance of unnecessary accelerations and decelerations between hole locations. In individual connecting trajectory instances within part drilling process, up to ∼62% connection time reduction was observed. Furthermore, a substantial improvement of up to ∼56% increase in the motion smoothness compared to using direct linear interpolation between the target hole locations due to abrupt start-stop motions between consecutive clusters and before repeated drilling of the same cluster.